Two SMARCAD1 Variants Causing Basan Syndrome in a Canadian and a Dutch Family - Youssef Elhaji; Tessa M.A. van Henten; Claudia A.L. Ruivenkamp; Mathew Nightingale; Gijs WE Santen; Lydia E. Vos; Peter R. Hull (JID Innovations, 2021)
Basan syndrome is an autosomal dominant genodermatosis characterized by congenital adermatoglyphia, transient congenital facial milia, neonatal acral bullae, and absent or reduced sweating. Basan syndrome is rare and has been reported in only 10 kindreds worldwide. It is caused by variants in the skin-specific isoform of SMARCAD1, which starts with an alternative exon 1. All reported variants, except for one large deletion, are point mutations within the donor splice site of the alternative exon 1. In this paper, we report two families with Basan syndrome and describe two SMARCAD1 variants. In one family, we have identified a complex structural variant (a deletion and a nontandem inverted duplication) using whole-genome optical mapping and whole-genome sequencing. Although this variant results in the removal of the first nine exons of SMARCAD1 and exon 1 of the skin-specific isoform, it manifested in the typical Basan phenotype. This suggests that unlike the skin-specific isoform, a single copy of full-length SMARCAD1 is sufficient for its respective function. In the second family, whole-exome sequencing revealed a deletion of 12 base pairs spanning the exon‒intron junction of the alternative exon 1 of the skin-specific SMARCAD1 isoform. In conclusion, we report two additional families with Basan syndrome and describe two SMARCAD1 pathogenic variants.